2021
DOI: 10.3390/jpm11111098
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association of Angiotensin Converting Enzyme-2 Gene Insertion/Deletion Polymorphism with Susceptibility to SARS-CoV-2, Hypertension, Coronary Artery Disease and COVID-19 Disease Mortality

Abstract: Background: The ongoing outbreak of SARS-CoV-2 represents a significant challenge to international health. Several reports have highlighted the importance of ACE2 on the pathogenesis of COVID-19. The spike protein of SARS-CoV-2 efficiently binds to the angiotensin-converting enzyme 2 (ACE2) receptors and facilitates virus entry into the host cell. In the present study, we hypothesize that a functional insertion/deletion polymorphism-rs4646994 I/D and rs4240157 T > C in the ACE gene could be associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 66 publications
(101 reference statements)
4
41
0
2
Order By: Relevance
“…However, the higher incidence of heterozygosity was reported among coronary artery disease patients who were younger than 50 years old with MI, which suggests that the contribution of genetics as a risk factor for MI occurrence became stronger among younger individuals—having none of the traditional risk factors, such as age. Similar results were reported by MM et al [ 46 ], which showed a significant correlation of ACE2-I/D genotypes with respect to age ( p < 0.035). On the other hand, there was a study done by Maria-Cristina Vladeanu et al [ 47 ] that reported no statistically significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the higher incidence of heterozygosity was reported among coronary artery disease patients who were younger than 50 years old with MI, which suggests that the contribution of genetics as a risk factor for MI occurrence became stronger among younger individuals—having none of the traditional risk factors, such as age. Similar results were reported by MM et al [ 46 ], which showed a significant correlation of ACE2-I/D genotypes with respect to age ( p < 0.035). On the other hand, there was a study done by Maria-Cristina Vladeanu et al [ 47 ] that reported no statistically significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…Studies noted that smoking and the D allele increase the superoxide anion formation and degradation of the nitric oxide that cause endothelial dysfunction favoring the occurrence of coronary disease [ 45 ]. Significant differences in the genotype distribution were detected only in those children with 2 or more affected grandparents This research is suggestive that a family history of CAD and ACE I/D genotype are bidirectionally linked, whereas recent data has shown that the DD genotype and a family history of CAD are independent risk factors for CAD, and, further, that the DD genotype may increase the risk to those who also share a family history of CAD [ 46 ].…”
Section: Discussionmentioning
confidence: 84%
“…Such discrepancies might be explained by population-specific differences, the additive role of other genes interacting with risk alleles or other mechanisms not assessed such as epigenetic modifiers ( 98 100 ). Concerning ACE rs4646994 the Del allele has been associated with increased ACE expression, higher enzyme activity and elevated production of angiotensin II ( 101 ). Despite ACE Del/Del genotype and Del allele have been associated with increased COVID-19 patient severity ( 101 103 ), our results failed to replicate these findings in the Colombian population.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning ACE rs4646994 the Del allele has been associated with increased ACE expression, higher enzyme activity and elevated production of angiotensin II ( 101 ). Despite ACE Del/Del genotype and Del allele have been associated with increased COVID-19 patient severity ( 101 103 ), our results failed to replicate these findings in the Colombian population. In agreement with our results, other studies have reported no association between ACE rs4646994 and COVID-19 severity ( 43 , 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted odds ratios (OR) and 95% confidence intervals (95% CI) associated with the risk of PCOS, were analyzed by logistic regression after controlling for a number of covariates and comparison with the reference group (healthy controls). Multivariate analysis was used to study the link between miR- 146a rs2910164 C>G and ESR1 PvuII-rs2234693 T>C genotyping and the susceptibility to disease in terms of odds ratios (ORs), risk ratios (RRs) and risk differences (RDs) with 95% confidence intervals (CIs) [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%